Comparison of two doses of heparin on outcome in off-pump coronary artery bypass surgery patients: A prospective randomized control study - Murali Chakravarthy; Dattatreya Prabhakumar; Patil Thimmannagowda; Jayaprakash Krishnamoorthy; Antony George; Vivek Jawali (Annals of Cardiac Anaesthesia, 2017)
Introduction: While off pump coronary artery bypass surgery is practiced with an intention to reduce the morbidity associated with cardiopulmonary bypass, the resultant ′hypercoagulability′ needs to be addressed. Complications such as cavitary thrombus possibly due to the hyper coagulability after off pump coronary artery bypass surgery have been described. Many clinicians use higher doses of heparin - up to 5 mg/kg in order to thwart this fear. Overall, there appears to be no consensus on the dose of heparin in off pump coronary artery bypass surgeries. Aim of the Study: The aim of the study was understand the differences in outcome of such as transfusion requirement, myocardial ischemia, and morbidity when two different doses were used for systemic heparinization. Methods: Elective patients scheduled for off pump coronary artery bypass surgery were included. Ongoing anti platelet medication was not an exclusion criteria, however, anti platelet medications were ceased about a week prior to surgery when possible. Thoracic epidural anesthesia was administered as an adjunct in patients who qualified for it. By computer generated randomization chart, patients were chosen to receive either 2 or 3 mg/kg of intravenous unfractioned heparin to achieve systemic heparinization with activated clotting time targeted at >240 secs. Intraoperative blood loss, postoperative blood loss, myocardial ischemic episodes, requirement of intraaortic balloon counter pulsation and transfusion requirement were analyzed. Results: Sixty two patients participated in the study. There was one conversion to cardiopulmonary bypass. The groups had comparable ACT at baseline (138.8 vs. 146.64 seconds, P = 0.12); 3 mg/kg group had significantly higher values after heparin, as expected. But after reversal with protamine, ACT and need for additional protamine was similar among the groups. Intraoperative (685.56 ± 241.42 ml vs. 675.15 ± 251.86 ml, P = 0.82) and postoperative blood loss (1906.29 ± 611.87 ml vs 1793.65 ± 663.54 ml , p value 0.49) were similar among the groups [Table 4]. The incidence of ECG changes of ischemia, arrhythmias, conversion to CPB, or need for intra-aortic balloon counter pulsation were not different. Conclusions: Use of either 2 or 3 mg/kg heparin for systemic heparinization in patients undergoing OPCAB did not affect the outcome.